Large Active Area, Low Capacitance Multi-Dot PIN Photodiode in 0.35 m CMOS Technology - S. S. Kohneh Poushi; B. Goll; K. Schneider-Hornstein; Horst Zimmermann (IEEE Photonics Journal, 2024)
This article presents a multi-dot PIN photodiode structure that addresses the inherent trade-off between the light-sensitive area and capacitance in conventional planar photodiodes commonly used in optical communication systems. This structure is a combination of several connected cathode dots and with a shared anode. The radial distribution of the electric field surrounding each cathode dot facilitates both vertical and peripheral charge collection, and accordingly, enables the region beneath and between the dots to function as a light-sensitive area with fast carrier drift. The key innovation of this work lies in the flexibility of the multi-dot structure for easy enlargement of the light-sensitive area by expanding the dot array, while still maintaining a small capacitance. Experimental results show that a 5 × 5 multi-dot PIN photodiode with a pitch of 20 $μ$ m corresponding to an active area of 100 $μ$ m × 100 $μ$ m achieves a capacitance of 48.8 fF, a responsivity of 0.294 A/W at a wavelength of 675 nm, and a bandwidth of 660 MHz at an operating voltage of 10 V. With a pitch of 15 $μ$ m that provides a light-sensitive area of 70 $μ$ m × 70 $μ$ m, the bandwidth increases to 930 MHz.